INFLUENCE OF ARTERIAL HYPERTENSION ON ORAL MUCOSAL AND PERIODONTAL HEALTH (International journal of artificial intelligence, 2026)
Arterial hypertension is among the most prevalent chronic cardiovascular diseases and is associated with systemic microcirculatory impairment that may affect oral tissues. This paper aims to analyze the impact of arterial hypertension on the oral mucosa and periodontal tissues from the perspective of pathophysiological mechanisms and clinical manifestations. Key pathways are discussed, including endothelial dysfunction, vascular remodeling, tissue ischemia and trophic disturbances, as well as the role of antihypertensive therapy in the development of xerostomia and periodontal changes. The most common oral findings in hypertensive patients are summarized: mucosal dryness, alterations in mucosal color and elasticity, increased susceptibility to microtrauma and delayed healing, along with a higher prevalence of inflammatory periodontal diseases. The relevance of an interdisciplinary approach and preventive strategies to reduce periodontal complications in hypertensive patients is emphasized.